Everyday resilience: Narratives of single refugee women with children. (September 2013) - Lenette, Caroline; Brough, Mark; Cox, Leonie
This article offers a critical exploration of the concept of resilience, which is largely conceptualized in the literature as an extraordinary atypical personal ability to revert or 'bounce back' to a point of equilibrium despite significant adversity. While resilience has been explored in a range of contexts, there is little recognition of resilience as a social process arising from mundane practices of everyday life and situated in person-environment interactions. Based on an ethnographic study among single refugee women with children in Brisbane, Australia, the women's stories on navigating everyday tensions and opportunities revealed how resilience was a process operating inter-subjectively in the social spaces connecting them to their environment. Far beyond the simplistic binaries of resilience versus non-resilient, we concern ourselves here with the everyday processual, person-environment nature of the concept. We argue that more attention should be paid to day-to-day pathways through which resilience outcomes are achieved, and that this has important implications for refugee mental health practice frameworks.